Global Travel in the Late Middle Ages: The Eyewitness Account of Johann Schiltberger. (May 2020) - Classen, Albrecht
Recent discussions have centred intensively on the question how to establish new cultural–historical perspectives that are no longer Eurocentric. Mediaevalists and Early Modernists have strongly endeavoured to grasp and to realise Global Mediaeval and Early Modern Studies, but despite many efforts, we are not easily getting away from traditional approaches, especially because many of our sources do not lend themselves quite so easily for that task. Whereas previous scholars have turned their attention primarily towards crusader and pilgrimage accounts, and then also towards some travelogues (Marco Polo), within the German context one early fifteenth-century text stands out that allows us to open the window wide towards a more global perspective, Hans Schiltberger's Reisebuch. This experienced tremendous popularity in the German-speaking lands far into the late seventeenth century, illustrating the life of a slave who was traversing many countries in the Middle East and even Northern Asia in military service. This account can in fact be regarded as a unique contribution in terms of the author's worldview and experiences. He was, involuntarily, one of the first European to report so extensively about those countries located east of the Holy Land and to discuss their political and military history.